Patient centered research to improve community involvement (PaRTICIpate) in diabetes self-management: a conference series for developing collaborations between researchers, stakeholders, and patients - Ashley S. Crumby; Erin R. Holmes; Meagen Rosenthal (SpringerOpen, 2018)
Abstract Background A patient-centered approach to research development is important to the creation of research evidence that is meaningful and beneficial to patients. Collaboration between patients, stakeholders, and researchers, where patients serve an integral role in all aspects of the research development process, is integral to achieving these twin objectives. Results This paper presents a unique approach to engaging patients and stakeholders in research by describing a conference series focused on meaningfully integrating patients in each phase of the project. Through three meeting phases, patients were not only introduced to patient-centered research (PCR) concepts, but they also led discussions about diabetes self-management and developed PCR questions. A total of 17 questions were developed represented by four main themes: communication, patient knowledge and perceptions, diabetes prevention, and diabetes management. Through patient feedback, three research questions were each identified as immediate priorities for development into research project proposals. Conclusion To our knowledge, the use of a conference series designed to teach patients about research, encourage collaboration across stakeholder groups, and write research questions has not been described in the literature. Moreover, this approach has proven successful in recruiting and retaining patient participation through the life of the project. This project has also identified a number of issues for consideration by future researchers looking to meaningfully engage patients in the development of research proposals.